Water removal from raw milk at the point of production - I. Cox; H. Dingeldein; Karen A. Schmidt (Kansas Agricultural Experiment Station Research Reports, 1999)
Milk processing plants are becoming fewer in number and larger in size. As a result, the distance the raw milk is transported from the point of production to the processing site increases. Because the major component in raw milk is water, the reduction of water at the production site would result in lower transportation costs as well as lower energy needs. Water can be removed from milk through a membrane filtration. This study showed that concentration of raw milk allowed for the microbes to partition into the milk solids fraction. Microbial numbers increased during refrigerated storage of this concentrated raw milk.; Dairy Day, 1999, Kansas State University, Manhattan, KS, 1999;
Keywords: Dairy Day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-136-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 842; Dairy; Dairy product; Ultrafiltration; Total plate counts; Coliform counts